2013
DOI: 10.4161/hv.23267
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the WC/rBS oral cholera vaccine in the prevention of traveler's diarrhea

Abstract: Objective: Traveler’s diarrhea (TD) is the most frequent disease among people from industrialized countries who travel to less developed ones, especially sub-Saharan Africa, Southern Asia and South America. The most common bacteria causing TD is enterotoxigenic Escherichia coli (ETEC). The WC/rBS cholera vaccine (Dukoral®) has been shown to induce cross-protection against ETEC by means of the B subunit of the cholera toxin. The aim of the study was to evaluate the effectiveness of the WC/rBS cholera vaccine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…19 In a recent non-randomized evaluation, the vaccine was found to provide 28% protection against TD. 20 Several vaccine candidates against ETEC are in various phases of development, including consideration of a combined ETEC/ Shigella vaccine, targeting both travelers and children living in endemic countries. 21 …”
Section: Pre-travel Preparationmentioning
confidence: 99%
“…19 In a recent non-randomized evaluation, the vaccine was found to provide 28% protection against TD. 20 Several vaccine candidates against ETEC are in various phases of development, including consideration of a combined ETEC/ Shigella vaccine, targeting both travelers and children living in endemic countries. 21 …”
Section: Pre-travel Preparationmentioning
confidence: 99%
“…The results suggest that WC/rBS vaccination of travelers to high-risk areas is associated with an absolute reduction of 28% in the risk of traveler's diarrhea. 30 In the study conducted by Aubry et al, 23 the percentages of other vaccinations were higher, especially for hepatitis B virus (4.1%), typhoid fever (37.1%), hepatitis A virus (41.5%), Japanese encephalitis (0.6%), and rabies (5.6%).…”
Section: Discussionmentioning
confidence: 92%
“…Besides pre-travel advice on general water and food precautions, the German Society for Tropical Medicine and International Health (DTG) recommends cholera vaccination for travellers to areas with current cholera outbreaks [11]. Oral cholera vaccination has also been shown to provide some protection against traveller's diarrhoea [12], but a recent systematic review of randomised controlled trials concluded that sufficient evidence is still lacking for its use to protect travellers against diarrhoea caused by enterotoxigenic Escherichia coli [13].…”
Section: Discussionmentioning
confidence: 99%